Biomarkers in the management of acute heart failure: state of the art and role in COVID‐19 era. (5th October 2021) - Aleksova, Aneta; Sinagra, Gianfranco; Beltrami, Antonio P.; Pierri, Alessandro; Ferro, Federico; Janjusevic, Milijana; Gagno, Giulia
Abstract: Acute heart failure (AHF) affects millions of people worldwide, and it is a potentially life‐threatening condition for which the cardiologist is more often brought into play. It is crucial to rapidly identify, among patients presenting with dyspnoea, those with AHF and to accurately stratify their risk, in order to define the appropriate setting of care, especially nowadays due to the coronavirus disease 2019 (COVID‐19) outbreak. Furthermore, with physical examination being limited by personal protective equipment, the use of new alternative diagnostic and prognostic tools could be of extreme importance. In this regard, usage of biomarkers, especially when combined (a multimarker approach) is beneficial for establishment of an accurate diagnosis, risk stratification and post‐discharge monitoring. This review highlights the use of both traditional biomarkers such as natriuretic peptides (NP) and troponin, and emerging biomarkers such as soluble suppression of tumourigenicity (sST2) and galectin‐3 (Gal‐3), from patients' emergency admission to discharge and follow‐up, to improve risk stratification and outcomes in terms of mortality and rehospitalization.